2010
DOI: 10.1101/gad.1942810
|View full text |Cite
|
Sign up to set email alerts
|

Defective erythroid differentiation in miR-451 mutant mice mediated by 14-3-3ζ

Abstract: Erythrocyte formation occurs throughout life in response to cytokine signaling. We show that microRNA-451 (miR-451) regulates erythropoiesis in vivo. Mice lacking miR-451 display a reduction in hematrocrit, an erythroid differentiation defect, and ineffective erythropoiesis in response to oxidative stress. 14-3-3ζ, an intracellular regulator of cytokine signaling that is repressed by miR-451, is up-regulated in miR-451−/− erythroblasts, and inhibition of 14-3-3ζ rescues their differentiation defect. These find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(190 citation statements)
references
References 28 publications
13
176
0
1
Order By: Relevance
“…The erythroid differentiation defect was observed in both miR-451 À/À mice and wild-type mice injected with a cholesterol-modified miR-451 antagomir, indicating that miR-451 plays a constitutive role in the differentiation of erythrocytes, rather than a role in embryonic development alone, and that both a chronic and transient loss of miR-451 function elicit the same phenotype (8). In zebrafish, miR-451 accelerates the rate of erythrocyte maturation, partly by repression of gata2, the gene encoding for GATA-2, a prostem cell transcription factor (6).…”
Section: Mir-451 In Erythropoiesismentioning
confidence: 94%
See 2 more Smart Citations
“…The erythroid differentiation defect was observed in both miR-451 À/À mice and wild-type mice injected with a cholesterol-modified miR-451 antagomir, indicating that miR-451 plays a constitutive role in the differentiation of erythrocytes, rather than a role in embryonic development alone, and that both a chronic and transient loss of miR-451 function elicit the same phenotype (8). In zebrafish, miR-451 accelerates the rate of erythrocyte maturation, partly by repression of gata2, the gene encoding for GATA-2, a prostem cell transcription factor (6).…”
Section: Mir-451 In Erythropoiesismentioning
confidence: 94%
“…At least some protective activities of miR-451 stem from its ability to directly suppress production of 14-3-3z, an intracellular regulator of cytokine signaling proteins that inhibits nuclear accumulation of the transcription factor FoxO3, a positive regulator of erythroid antioxidant genes (8,9). The miR-451/14-3-3z/FoxO3 regulatory axis might have potential implications beyond erythropoiesis.…”
Section: Mir-451 In Erythropoiesismentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatics analysis failed to predict and identify CAB39, LKB1 and AMPK as miR-451 target genes (GBandres et al, 2009;odlewski et al, 2010;Patrick et al, 2010;Li et al, 2011;Tian et al, 2012;Wang et al, 2013). The Western blot results showed that miR-451 over-expression decreased expression of miR-451 target genes, CAB39, LKB1 and AMPK (Figure3).…”
Section: Detection Of Mir-451 Target Genesmentioning
confidence: 99%
“…In addition, the percentage of CD41 + cells was upregulated upon induction of miR-146b ( Figure 5B), suggesting a role of this miRNA in primitive hematopoiesis. Surprisingly, there was no obvious alteration in formation of CD71 high population upon enforced expression of miR-144/451, a previously reported miRNA in the erythroid formation (Patrick et al, 2010). It is possible that sole overexpression of miR-144/451 was not sufficient to induce primitive erythroid fate specification during ESC differentiation.…”
Section: Differential Effects Of Micrornas On Hematopoiesis During Esmentioning
confidence: 76%